An extended n-player network game and simulation of four investment strategies on a complex innovation network - Wen Zhou; Nikita Koptyug; Shutao Ye; Yifan Jia; Xiaolong Lu (Research Institute of Industrial Economics (IFN), 2015)
As computer science and complex network theory develop, non-cooperative games and their formation and application on complex networks have been important research topics. In the inter-firm innovation network, it is a typical game behavior for firms to invest in their alliance partners. Accounting for the possibility that firms can be resource constrained, this paper analyzes a coordination game using the Nash bargaining solution as allocation rules between firms in an inter-firm innovation network. We build an extended inter-firm n-player game based on nonidealized conditions, describe four investment strategies and simulate the strategies on an inter-firm innovation network in order to compare their performance. By analyzing the results of our experiments, we find that our proposed greedy strategy is the best-performing in most situations. We hope this study provides a theoretical insight into how firms make investment decisions.
Keywords: C72; C81; C82; D81; L14; 330; Complex Networks; Game Theory; Innovation; Innovation Network; Nash Equilibrium